MANAJEMEN PEMBIAYAAN PENDIDIKAN PADA SMK NEGERI DI KABUPATEN ACEH BESAR - Baihaqi .; Nasir Usman; Cut Zahri (Jurnal Administrasi Pendidikan : Program Pascasarjana Unsyiah, 2012)
Abstract: The management of education funding is the process of setting up and managing costs effectively and efficiently in education financing business. The cost of education is a very important component in education. The process of education cannot work without the support costs. The purpose of this study to Describe and analyze matters relating to: the budget planrevenue expenditure, the use of education funding, and oversight of education funding. The method used in this study was a descriptive qualitative approach. Data collection techniques used were interviews, observation, and documentation. Subjects: principals, vice principals, school treasurers, and school committees. The results showed that: the budgeting process undertaken by the principal, with the involvement of the assistant principal, department chair, treasurer, senior teachers, and school committees. The use of education funding in terms of the financial side, that all types of expenditures for education activities in schools should be shared by both the principal and the school internal parties involved in the process of preparing budgets. Oversight of education funding in Aceh Besar district SMK carried out by the principal and vice principal. Control system is by way of observing each income andexpenditure of funds. Monitoring or examination by indirect observations such as every expenditure of funds must be approved by the principal or bursar. Audits are also performed by examining the financial reports on all activities performed, awarded by the vice-principal or bursar.Key words: Management and Financing of Education